Effect of Calcium Nitrate on Chlorophyll-Based Biotransducer Characterization of Arthrospira platensis Gomont - Mulia Safrida Sari; Rachmad Almi Putra; Yonadiah Dwitya; M Ari Fahril (SEAMEO BIOTROP, 2025)
ARTICLE HIGLIGHTS- Calcium nitrate is utilized to enhance the growth and chlorophyll quality of Arthrospira platensis Gomont, aiming to maximize its potential as a biotransducer molecule.- Biomass productivity was monitored every three days during a 15-day cultivation period, with specific attention to biomass accumulation and specific growth rates during the stationary phase.- Chlorophyll concentrations (chlorophyll a, chlorophyll b, and total chlorophyll) were measured using a UV-Vis spectrophotometer at wavelengths of 648 nm and 664 nm.- Fourier-transform infrared spectroscopy (FTIR) was performed on chlorophyll extracts to assess molecular binding capacity, reinforcing Arthrospira platensis Gomont’s potential as a biotransducer.- A concentration of 4.5 g/L of calcium nitrate, in combination with 35 ppt salinity, was found to be optimal for enhancing chlorophyll production during cultivation.ABSTRACTThe aim of this study is to investigate the potential of calcium nitrate as a specific nutrient capable of enhancing the chlorophyll content and optimizating the biotransducer characterization in Arthrospira platensis Gomont. The experimental design employed a Completely Randomized Design (CRD) with Two Factors, consisting of 12 treatments and 3 replications. Each research group was conditioned with varying salinity levels: 15 ppt (S15), 25 ppt (S25), and 35 ppt (S35). In the treatment groups, calcium nitrate was added at different concentrations: 2.5 g/L (P1), 3.5 g/L (P2), and 4.5 g/L (P3). Biomass accumulation and specific growth rate were monitored and data were collected throughout the experiment. At the end of the treatment period, chlorophyll was extracted and its concentration was measured using UV-Vis Spectrophotometry and FTIR analysis. The results indicated that the addition of calcium nitrate 4.5 g/L combined with 35 ppt salinity increased the average biomass productivity over 15 days by 5.1 g/L, with a specific growth rate in the stationary phase of 0.12 per day. Supplementation of calcium nitrate 4.5 g/L in 35 ppt salinity was found to increase total chlorophyll concentration to 70.15 μg/mL, further supporting its potential as a supplementary nutrient to enhance the biotransducer properties with five key functional groups for the stability and binding affinity of analyte molecules in SPR application.